2017
DOI: 10.1016/j.ijnurstu.2017.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Self-management support at the end of life: Patients’, carers’ and professionals’ perspectives on managing medicines

Abstract: Background: Pain is a frequently reported symptom by patients approaching the end of life and wellestablished that patients and carers hold fears relating to opioids, and experience side effects related to their use. The management of medicines is intrinsic to achieving effective pain relief. The concept of self-management support whilst well characterised in the context of chronic illness has not been elaborated with respect to end of life care. Aim: To identify patient, carer and professional views on the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Four quantitative 37 , 43 , 56 , 57 and 15 qualitative studies 39 , 45 48 , 50 , 52 , 55 , 59 63 , 65 , 66 indicated that many patients sought support from relatives and friends (28%–94% in the quantitative studies). This was mentioned as an effective strategy by 61% and 100% of the patients in two quantitative studies on pain management and general symptom management, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four quantitative 37 , 43 , 56 , 57 and 15 qualitative studies 39 , 45 48 , 50 , 52 , 55 , 59 63 , 65 , 66 indicated that many patients sought support from relatives and friends (28%–94% in the quantitative studies). This was mentioned as an effective strategy by 61% and 100% of the patients in two quantitative studies on pain management and general symptom management, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 45 48 , 62 Patients considered maintaining or intensifying relationships with relatives important, because it gave them emotional strength, 45 , 57 , 60 , 65 provided distraction from their cancer symptoms, 62 made them feel important and helpful to others, 62 protected their identities and usual social roles 48 and enabled them to rely on relatives in case their condition would worsen. 39 In several qualitative studies, however, patients also mentioned that they found it difficult to accept or ask for support from relatives and friends, because they did not want to be a burden. 55 , 59 63 , 65 Some of them only asked for help when they could no longer perform their usual activities 50 , 60 , 61 , 63 , 66 or restricted their social contacts to close relatives or moments when they felt good.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study research questions were derived from patient experiences reported in our previous research [1] and through consultation with local groups of palliative care patients and unpaid carers caring for a family member in the last year of life. The study team includes a Public and Patient Involvement co-applicant, and the Study Scientific Committee includes two Patient and Public Involvement members, whose views have helped shape the survey questions.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
“…Patients are commonly managing symptoms at home and may experience extensive barriers to accessing essential medicines: our recent study suggested prescription, dispensing, supply and associated information given about medicines 1 are difficult, complex, demanding, lack co-ordination, and involve a multiplicity of professionals [1]. Problems were identified with each element of the access processranging from the time-consuming nature of obtaining new prescriptions, lack of pharmacy stock of medicines required, to limited medicines information and misconceptions [1]. There is very limited research internationally on experiences of accessing medicines for community palliative care, but a few small studies are suggestive of problems.…”
Section: Introductionmentioning
confidence: 99%